EFFICIENCY OF ORGANIC COMPOST IN THE DEVELOPMENT OF Moringa oleifera LAM. SEEDLINGS - Freitas Dantas Gouveia, Daniel; Neves do Nascimento, Marilza; da Silva Leite, Romeu (Floresta, 2023)
This study aimed to evaluate the efficiency of organic compost produced through composting in the development of Moringa oleifera seedlings. The experiment was carried out in a greenhouse in Feira de Santana- BA, Brazil. The design was randomized blocks (RBD), with seven treatments per block and four replicates. The following treatments were tested: commercial substrate; sand (S); S/organic compost (OC) 80/20; S/OC 60/40; S/OC 40/60; S/OC 20/80; S/OC 0/100. The organic compost was formed by pruning residues and vegetable remains that were not cooked. The addition of organic compost promoted the highest means for the parameters height, number of leaves, height/collar diameter ratio, root dry mass and shoot dry mass. For leaf area, height/shoot dry mass ratio and collar diameter, the proportions of the compost had no influence. Higher means of parameters such as tuberous root length and diameter and tuberous structure dry mass were observed in the commercial substrate, which may indicate stress in seedlings of this treatment. Substrates with a lower proportion of organic compost are more suitable for the production of M. oleifera seedlings.